A new species of Halictophagus (Insecta: Strepsiptera: Halictophagidae) from Texas, and a checklist of Strepsiptera from the United States and Canada - Kathirithamby, Jeyaraney; Taylor, Steven J. (Zootaxa, 2005)
A new species of Halictophagidae (Insecta: Strepsiptera), Halictophagus forthoodiensis Kathirithamby & Taylor, is described from Texas, USA. We also present a key to 5 families, and a check-list of 11 genera and 84 species of Strepsiptera known from USA and Canada.